2021
DOI: 10.1158/2326-6066.cir-20-0555
|View full text |Cite
|
Sign up to set email alerts
|

The IKZF1–IRF4/IRF5 Axis Controls Polarization of Myeloma-Associated Macrophages

Abstract: The bone marrow niche has a pivotal role in progression, survival, and drug resistance of multiple myeloma cells. Therefore, it is important to develop means for targeting the multiple myeloma bone marrow microenvironment. Myeloma-associated macrophages (MAM) in the bone marrow niche are M2 like. They provide nurturing signals to multiple myeloma cells and promote immune escape. Reprogramming M2-like macrophages toward a tumoricidal M1 phenotype represents an intriguing therapeutic strategy. This is especially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…On these premises, several macrophages depleting/reprogramming therapies are under active investigation. The IKZF1-IRF4/IRF5 axis is necessary to drive the pro-tumoral polarization of macrophages, and its targeting exerted by IMiDs demonstrated the recovery of an anti-tumor functional status [44]. This event could contribute to the brilliant clinical results achieved by the combination of IMiDs with myeloma targeting monoclonal antibodies such as daratumumab and isatuximab, whose activity relies in part on the presence of functional macrophages [11,45,46].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…On these premises, several macrophages depleting/reprogramming therapies are under active investigation. The IKZF1-IRF4/IRF5 axis is necessary to drive the pro-tumoral polarization of macrophages, and its targeting exerted by IMiDs demonstrated the recovery of an anti-tumor functional status [44]. This event could contribute to the brilliant clinical results achieved by the combination of IMiDs with myeloma targeting monoclonal antibodies such as daratumumab and isatuximab, whose activity relies in part on the presence of functional macrophages [11,45,46].…”
Section: Monocytes/macrophagesmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 4, 2021. ; https://doi.org/10.1101/2021.10.04.462880 doi: bioRxiv preprint iNOS expression in macrophages, and loss of Ikaros may promote repolarization to proinflammatory macrophages (51,52). Therefore, the role of Ikaros in macrophages and microglia is controversial and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lenalidomide that was recently approved for patients with multiple myeloma [252] recruits the E3 ligase cereblon to target the Ikaros transcription factor (IKZF1). However, it has been recently observed that IKZF1 plays a pivotal role in promoting macrophages' skew towards a pro-tumour phenotype, and lenalidomide interrupts this switch, supporting their repolarisation towards a tumouricidal one [253]. New "degraders" that can target tumour cells and support myeloid cell "re-education" are enlisted in this development pipeline.…”
Section: New Perspectives In Mdsc-targeting Approachesmentioning
confidence: 99%